Design, modeling and control of a flying vehicle with a single moving part that can be positioned anywhere in space. (August 2019) - Zhang, Weixuan; Mueller, Mark W.; D'Andrea, Raffaello
Abstract: This paper presents a novel type of flying vehicle called the Monospinner, which has only one moving part, the propeller, and is yet able to hover and fully control its position. Its translational and attitude dynamics are formulated as a twelve-dimensional state space system, which may be linearized to a linear time-invariant system amenable to controllability analysis, controller synthesis, and vehicle design. It is shown that the linearized system may be both horizontally and vertically controllable in position after removing its yaw state, and in particular, this is shown for the case of a vehicle with the shape of a planar object and an offset thrust location (with respect to its center of mass). The vehicle's mass distribution is designed based on two robustness metrics: the ability to maintain hover under perturbations by means of Monte-Carlo nonlinear simulation, and the probability of input saturation based on a stochastic model. Experiments are conducted for the resulting vehicle and controller. The equilibrium of the resulting system has a large region of attraction such that it recovers after being thrown into the air like a frisbee.